Por uma educação musical humanizadora: o ensino coletivo de música a várias mãos - Oliveira, Pedro Augusto Dutra de (2014)
This research took place in a Social Project, named Guri, in Batatais, a city of the state of São Paulo . The Guri Project is a socio-cultural music education program, mostly maintained by the State Government. The specific objectives of the research were to identify and describe musical practices that occur in different spaces of the building where the Project is installed. After identifying such practices, the educational processes was described, based in the students relationships, focusing their involvement with music. The methodological framework was based in the understanding on how that everyone learns in harmony, considering the social and the musical view. Three groups of musical practices have been identified, with the inclusion of the researcher in one of them within approximately three months, in order to participate and identify educational processes that occur among the students during the music practice. The first practice observed was among the percussion set, in the orchestra rehearsals during the Project . The second practice observed was the meetings of two little girls made, every week, in one of the empty rooms of the building, in an extra class time. The third and final insertion occurred in group activities developed in a string class. After identifying the educational processes, analysis and discussion the data, such processes were separated into the following categories: DIALOGUE AND MUSICAL SPEECH; COLABORATION AND LEARNING TOGETHER; COLABORATION, AUTONOMY, MUSIC PRACTICE AND THEIR RESULTS. The study aims to contribute in the field of music education, specifically to produce knowledge about music education from the perspective of humanizing education. For instance, we intended to understand how the students develop relationship between them and the music, how was being educated in community, considering the social and musical autonomy of the students.